Kenya : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Joint Staff Advisory Note (JSAN) reviews the Kenya Vision 2030 (the Vision) First Medium-Term Plan (MTP) 2008-12 prepared by the government of Kenya. IMF staff finds that the objectives of the MTP are generally compelling and well considered on a sector-by-sector basis, but less so on a holistic basis. The sector-specific plans are generally compatible with the government's objective of meeting the Millennium Development Goals. However, the overall plan suffers from two weaknesses. This means that some of the headline targets may not be met.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet